Just Drink a Glass of Water? Effects of Bicarbonate–Sulfate–Calcium–Magnesium Water on the Gut–Liver Axis - Gravina, Antonietta Gerarda; Romeo, Mario; Pellegrino, Raffaele; Tuccillo, Concetta; Federico, Alessandro; Loguercio, Carmelina (Frontiers in Pharmacology, 2022)
Background and aim: Fonte Essenziale ® water is a bicarbonate-sulfate-calcium-magnesium water, low in sodium recognized by the Italian health care system in hydropinotherapy and hepatobiliary dyspepsia therapy. We wanted to explore its effects on the gut-liver axis and microbiota in nonalcoholic fatty liver disease patients. Patients and methods: We considered for enrollment 70 patients of which four were excluded. We finally enrolled 55 patients with ultrasound-documented steatosis (SPs+) and 11 patients without it (SPs-). They then drank 400 ml of water for six months in the morning on an empty stomach. Routine haematochemical and metabolic parameters, oxidative stress parameters, gastrointestinal hormone levels, and fecal parameters of the gut microbiota were evaluated at three different assessment times, at baseline (T0), after six months (T6), and after a further 6 months of water washout (T12). We lost, in follow-up, 4 (T6) and 22 (T12) patients. Results: Between T0-T6, we observed a significant Futuin A and Selenoprotein A decrease and a GLP-1 and PYY increase in SPs+ and the same for Futuin A and GLP-1 in SPs-. Effects were lost at T12. In SPs+, between T0-T12 and T6-12 a significant reduction in Blautia and between T0-T12 of Collinsella unc. as well as an increase, between T0-T12 and T6-12 in Subdoligranulum and Dorea was observed. None of the bacterial strains we analyzed varied significantly in the SPs- population. Conclusions: These results indicate water's beneficial effects on gastrointestinal hormones and hence on the gut-liver axis in the period in which subjects drank water, both in SPs- and in SPs+.